Burden of disease attributable to Risk Factors in Brazil: an analysis of national and subnational estimates from the 2019 Global Burden of Disease study - Malta,Deborah Carvalho (2022)
Abstract INTRODUCTION: Monitoring trends in risk factors (RFs) and the burden of diseases attributable to exposure to RFs is an important measure to identify public health advances and current inadequate efforts. Objective: Analyze the global burden of disease attributable to exposure RFs in Brazil, and its changes from 1990 to 2019, according to the sex and age group. METHODS: This study used data from the Global Burden of Disease study. The Summary Exposure Value, which represents weighted prevalence by risk, was used to estimate exposure to RFs. The mortality and DALYs (Disability Adjusted Life Years) measurements were used to estimate the burden of diseases. For comparisons by year and between Brazilian states, age-standardized rates were used. RESULTS: Arterial hypertension was the factor responsible for most deaths in both sexes. For DALYs, the most important RF was the high body mass index (BMI) for women and alcohol consumption for men. Smoking had a substantial reduction in the attributable burden of deaths in the period. An important reduction was identified in the exposure to RFs related to socioeconomic development, such as unsafe water, lack of sanitation, and child malnutrition. Metabolic RFs, such as high BMI, hypertension, and alcohol consumption showed an increase in the attributable burden. CONCLUSIONS: Our findings point to an increase in metabolic RFs, which are the main RFs for mortality and DALYs. These results can help to consolidate and strengthen public policies that promote healthy lifestyles, thus reducing disease and death.